Politeness Strategy in Interlanguage Pragmatics of Complaints by International Students - Idda Astia (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The study aims to investigate the speech acts of international students in Universitas Muhammadiyah Surabaya in giving complaints. This study focuses on the complaint speech acts and the politeness strategy which are produced by International students who have different cultural background. This study used qualitative approach because it observed the complaints speech acts of International students in applying the politeness strategy. There were four participants consist of three males and one female. They came from Mexico, Thailand, East Timor and Togo. The data were taken by purposive sampling. The data contained the complaints which were delivered by the international students conducted through chatting on WhatsApp. Those were collected, categorized, analyzed and concluded. Finally, it is inferred that complaint speech acts which used by showing irritation or disapproval expression and blame. Thus, in politeness strategy, social distance (age and status) and cultural background induce the way of giving complaints. Bald on record politeness strategy is used in the culture which has directness term. Moreover, negative politeness is applied by the complainer who has culture in indirectness term. Bald on record politeness strategy has the chance for face threatening acts (FTA) in the other hand, negative politeness strategy can avoid the FTA.